1999
DOI: 10.1128/aem.65.4.1644-1651.1999
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Action of Acarbose Hydrolysis and Transglycosylation Catalyzed by a Thermostable Maltogenic Amylase, the Gene for Which Was Cloned from a Thermus Strain

Abstract: A maltogenic amylase gene was cloned in Escherichia coli from a gram-negative thermophilic bacterium,Thermus strain IM6501. The gene encoded an enzyme (ThMA) with a molecular mass of 68 kDa which was expressed by the expression vector p6xHis119. The optimal temperature of ThMA was 60°C, which was higher than those of other maltogenic amylases reported so far. Thermal inactivation kinetic analysis of ThMA indicated that it was stabilized in the presence of 10 mM EDTA. ThMA harbored both hydrolysis and transglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…The difference in molecular masses was due to the presence of the six-histidine tag and extra two amino acids (methionine and glutamic acid) attached to the N-terminus of the recombinant protein. The molecular mass of LGMA is much lower than that of other extracellular a-amylases found in LAB, such as L. amlylovorus (140 kDa), L. plantarum (230 kDa) and L. amlylophilus (100 kDa), but is similar to other MAases from Bacillus and Thermus strains [3,[10][11][12]. Gel permeation chromatography revealed that LGMA is present at a molecular mass of 211 kDa, implying that LGMA may exist in a functional tetrameric form in solution (Fig.…”
Section: Characterization Of the Recombinant Lgmamentioning
confidence: 84%
See 4 more Smart Citations
“…The difference in molecular masses was due to the presence of the six-histidine tag and extra two amino acids (methionine and glutamic acid) attached to the N-terminus of the recombinant protein. The molecular mass of LGMA is much lower than that of other extracellular a-amylases found in LAB, such as L. amlylovorus (140 kDa), L. plantarum (230 kDa) and L. amlylophilus (100 kDa), but is similar to other MAases from Bacillus and Thermus strains [3,[10][11][12]. Gel permeation chromatography revealed that LGMA is present at a molecular mass of 211 kDa, implying that LGMA may exist in a functional tetrameric form in solution (Fig.…”
Section: Characterization Of the Recombinant Lgmamentioning
confidence: 84%
“…lactis, 44% with the MAase of Bacillus subtilis (BBMA) [15] and 44% with the MAase of Thermus sp. (ThMA) [3].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations